A Comprehensive Meta-Analysis of Cassava Addition in a Buffalo Diet: In Vivo Investigations on Performance and Rumen Health - Amirul, F. M. A.; Mazlan, N. A.; Sadarman, S.; Rusli, N. D.; Sholikin, M. M.; Irawan, A.; Febrina, D.; Qomariah, N.; Nurfitriani, R. A.; Aditya, S.; Jayanegara, A.; Saad, M. Z.; Adli, D. N.; Hassim, H. A. (Tropical Animal Science Journal, 2025)
This meta-analysis compiles data on buffalo consumption of cassava as a feed ingredient to evaluate its impact on in vivo rumen fermentation, feed intake, nutrient intake, growth performance, digestibility, nitrogen metabolism, haematology, microbiology, and milk yield. A systematic search of Scopus and Web of Science identified 19 in vivo experiments. Cassava varieties were categorized as by-products, foliage, and roots, while buffaloes were stratified based on management system, breed, and sex. A linear mixed model was applied to estimate the effects of cassava inclusion. The findings indicated feed and nutrient intake, particularly crude protein intake and nitrogen retention, increased significantly (p<0.05), while crude protein digestibility showed no significant difference. Microbiological parameters, including total bacterial and fungal counts, also increased significantly (p<0.05), whereas methane production after 24 hours declined significantly (p<0.05). Although production parameters such as body weight, feed conversion, and milk yield were not significantly affected, a trend toward improvement was observed, except for feed conversion. Cassava root and foliage exhibited the highest digestibility and nitrogen retention compared to by-product (p<0.05). A restricted feeding system resulted in higher ammonia (NH3-N) concentrations, protozoa count, and proteolytic and cellulolytic microbial populations compared to ad libitum feeding and an extensive system (p<0.05). Murrah buffaloes showed greater feed intake, while male buffaloes demonstrated higher digestibility (p<0.05). In conclusion, dietary cassava, approximately 1.5% to 20.5% DM, potentially stimulates rumen fermentation, nutrient intake, digestibility, and microbiology but has only a modest effect on production parameters. High cassava inclusion may reduce feed acceptability, thereby decreasing feed efficiency.